Implementasi Metode Halaqah Pembelajaran Tahfidz Qur’an Peserta Didik Kelas 1 di MI Terpadu Tahfizhul Qur’an Al-Ma’shum - Kinesti, Rakanita Dyah Ayu; Efendi, Faza Dzulfikar; Kholilah, Nany; Nandifa, Aprilia (Lembaga Yasin AlSys, 2023)
The tahfidz al-Qur'an learning method, along with the development of the times has experienced various innovations. Various methods and models of reciting the Qur'an have emerged which refer to practical, effective and efficient. As was done by the Madrasah Ibtidaiyah Integrated Taḥfīẓhul Qur'an Al-Ma'shum. This study aims to determine the implementation, interest in learning, as well as the features and weaknesses of the halaqah method in learning tahfidz al-Qur'an. This study uses qualitative analysis with data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The research was conducted on teachers and grade 1 students of Madrasah Ibtidaiyah Integrated Tahfizhul Qur'an Al-Ma'shum using data collection methods in the form of interviews, observation, and documentation. From this study it was found that the implementation of the halaqah method in learning the tahfidz Qur'an of class 1 students of Madrasah Ibtidaiyah Integrated Tahfizhul Qur'an Al-Ma'shum makes students more active and like learning tahfidz Qur'an. Besides that, it can provide opportunities for students to study together with their group mates so that students' abilities can be honed properly.